The Influence of Celebrity Endorser And Word Of Mouth On Purchasing Decisions MS Glow Skincare Products in Bekasi Regency - Purti Amelia Dewi; Nelly Martini (Primanomics : Jurnal Ekonomi & Bisnis, 2023)
The research conducted aims to identify, analyze, and explain how the partial and simultaneous influence between celebrity endorsers and word of mouth on the decision to purchase Ms Glow Di Skincare Products Regency Bekasi. Study this use type study quantitative with method descriptive and verification. Population on study this that is visitors to MS Glow Distributor Bekasi Regency in 2022. Population year 2022 searching for use trend linear . Sample which will in test in study this amount 320 people with withdrawal sample use slovin . Study this use technique Non probability sampling with purposive technique . Data analysis techniques use analysis of the scale and range analysis path (Path analysis) with tool analysis software SPSS 21 for windows. Based on results study which conducted showing The correlation coefficient between celebrity endorser variable and word of mouth of 0.589 correlation level currently, enough strong. Influence Partial celebrities endorser to decision purchase as big 3.8% whereas word of mouth to decision purchase own contribution which more big that is as big 27.5%, in a manner simultaneous total influence celebrities endorser and word of mouth to decision purchase as big 0.436% whereas the rest as big 56.4% is influence else that no be measured on study this.